Network analysis of loneliness, mental, and physical health in Czech adolescents - Meier, Zdenek; Helvich, Jakub; Furstova, Jana; Novak, Lukas; Purova, Dana; Zidkova, Radka; Tavel, Peter (Child and adolescent psychiatry and mental health, 2025)
BACKGROUND: The increasing urgency to address rising loneliness among adolescents has become a critical issue, underscoring the need for further studies on its association with mental and physical health. The objective was to examine the changes in loneliness and its relation to mental and physical health issues in three adolescent age groups. METHODS: A total sample of 14,588 Czech pupils (50.7% boys, mean age 13.6 ± 1.7 years) in grades 5, 7 and 9 was used from a representative dataset of the Health Behaviour in School-aged Children (HBSC) study. The network analysis based on undirected graphical models was used as an exploratory technique to assess and test the structure of the data. RESULTS: The association between loneliness and health decreased with age. There was a significant positive association between loneliness, feeling low, and irritability. No significant direct association between loneliness and physical health complaints was found. CONCLUSION: Further studies, preferably of longitudinal character, are needed to confirm the changes in associations between loneliness and mental and physical health outcomes.
Keywords: Mental health; Loneliness; Adolescents; Network analysis; HBSC; Physical health